PERANCANGAN GAME 3D VIRTUAL PET “MoAR” BERBASIS ANDROID - Cliffen Allen; Jeanny Pragantha; Darius Andana H (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Some of the reasons people wants a pet is quite simple, it’s cuteness or for a companion to accompany their everyday life, but not everyone can own a pet. There are so many reasons to say no to breeding a pet start from the the money needed for it’s needs, the fuss for cleaning up, or just because the neighborhood doesn’t let any pet existence. “MoAR” is created to simulate pet breeding experience for those who wants a pet yet cannot. “MoAR” is a 3D virtual game made with Blender for creating 3D and 2D objects, Unity3D as the game engine, and written in C# for Android based smartphone. Key words 3D Game, Android, Blender, C#, Unity3D